Reliability and validity of the mandarin version of the supportive care needs survey short-form (SCNS-SF34) and the head and neck cancer-specific supportive care needs (SCNS-HNC) module - Jianxia Lyu; Li Yin; Ping Cheng; Bin Li; Shanshan Peng; Chunlian Yang; Jing Yang; Haixin Liang; Qinghua Jiang (BMC, 2020)
Abstract Background This study aimed to translate the English version of the supportive care needs scale of head and neck cancer patients (SCNS-HNC) questionnaire into Mandarin and to test the reliability and validity of the SCNS-SF34 and SCNS-HNC module in head and neck cancer patients. Methods The Mandarin version of the Supportive Care Needs Survey Short-Form (SCNS-SF34) and SCNS-HNC scales were used to assess 206 patients with head and neck cancer in Chengdu, China. Among them, 51 patients were re-tested 2 or 3 days after the first survey. The internal consistency of the scale was evaluated by Cronbach's alpha coefficient, the retest reliability of the scale was evaluated by retest correlation coefficient r, the structural validity of the scale was evaluated by exploratory factor analysis, and the ceiling and floor effects of the scale were evaluated. Results The Mandarin version of the SCNS-HNC had Cronbach's alpha coefficients greater than 0.700 (0.737 ≤ 0.962) for all of the domains. Except for the psychological demand dimension (r = 0.674) of the SCNS-SF34 scale, the retest reliability of the other domains was greater than 0.8. Three common factors were extracted by exploratory factor analysis, and the cumulative variance contribution rate was 64.39%. Conclusions The Mandarin version of the SCNS-SF34 and SCNS-HNC demonstrated satisfactory reliability and validity and is able to measure the supportive care needs of Chinese patients with head and neck cancer. Trial registration ChiCTR, ChiCTR1900026635 . Registered 16 October 2019- Retrospectively registered.